CAR modulates plasma membrane nano‐organization and immune signaling downstream of RALF1‐FERONIA signaling pathway. Issue 6 (9th January 2023) - Chen, Weijun; Zhou, Huina; Xu, Fan; Yu, Meng; Coego, Alberto; Rodriguez, Lesia; Lu, Yuqing; Xie, Qijun; Fu, Qiong; Chen, Jia; Xu, Guoyun; Wu, Dousheng; et al.
Summary: In Arabidopsis, the receptor‐like kinase (RLK) FERONIA (FER) senses peptide ligands in the plasma membrane (PM), modulates plant growth and development, and integrates biotic and abiotic stress signaling for downstream adaptive responses. However, the molecular interplay of these diverse processes is largely unknown. Here, we show that FER, the receptor of Rapid Alkalinization Factor 1 (RALF1), physically interacts with C2 domain ABA‐related (CAR) proteins to control the nano‐organization of the PM. During this process, the RALF1‐FER pathway upregulates CAR protein translation, and then more CAR proteins are recruited to the PM. This acts as a rapid feedforward loop that stabilizes the PM liquid‐ordered phase. FER interacts with and phosphorylates CARs, thereby reducing their lipid‐binding ability and breaking the feedback regulation at later time points. The formation of the flg22‐induced FLS2‐BAK1 immune complex, which depends on the integrity of FER‐containing nanodomains, is impaired in fer and pentuple car14569 mutant. Together, we propose that the FER‐CAR module controls the formation of PM nano‐organization during RALF signaling through a self‐contained amplifying loop including both positive and negative feedback.